Contemporary Indigenous Arts in the Classroom - Garneau, David; Nadeau, Stephanie; Dumais, Doug; Cross, Wahsontiio (Galerie d'art d'Ottawa = Ottawa Art Gallery, 2018)
Section: pages cm.
Keywords: 1-Histoire de l'art; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Paix, pouvoir et droiture. Un manifeste autochtone - Alfred, Taiaiake (Éditions Hannenorak, 2014)
Paix, pouvoir et droiture : un manifeste autochtone, qui tire sa structure des chants rituels de la cérémonie de condoléances rotinohshonni, appelle toutes les Premières Nations à prêter attention aux messages des ancêtres afin de développer une philosophie visant à contrer l'assimilation. L'essai de Taiaiake Alfred est un véritable plaidoyer en faveur de droits et de l'autodétermination des peuples autochtones. Ce manifeste se veut avant-gardiste proposant des pistes de réflexion inédites ayant significativement participé à améliorer la compréhension des enjeux des Première Nations de l'Amérique du Nord.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Indigenous and Decolonizing Studies in Education: Mapping the Long View - Tuhiwai Smith, Linda; Tuck, Eve; Yang, K. Wayne (Routledge, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.–publisher's description.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Native Studies Keywords - Teves, Stephanie N.; Smith, Andrea; Raheja, Michelle H. (The University of Arizona Press, 2015)
"Native Studies Keywords explores selected concepts in Native studies and the words commonly used to describe them, words whose meanings have been insufficiently examined. This edited volume focuses on the following eight concepts : sovereignty, land, indigeneity, nation, blood, tradition, colonialism, and indigenous knowledge. Each section includes three or four essays and provides definitions, meanings, and significance to the concept, lending a historical, social, and political context. Take sovereignty, for example. The word has served as the battle cry for social justice in Indian Country. But what is the meaning of sovereignty? Native peoples with diverse political beliefs all might say they support sovereignty-without understanding fully the meaning and implications packed in the word. The field of Native studies is filled with many such words whose meanings are presumed, rather than articulated or debated. Consequently, the foundational terms within Native studies always have multiple and conflicting meanings. These terms carry the colonial baggage that has accrued from centuries of contested words. Native Studies Keywords is a genealogical project that looks at the history of words that claim to have no history. It is the first book to examine the foundational concepts of Native American studies, offering multiple perspectives and opening a critical new conversation"–Résumé du site web de l'éditeur
Section: xi, 356 pages : illustrations ; 23 cm.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Whose Land Is It Anyway?: A Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Fédération of Post-Secondary Education of BC, 2018)
Whose Land Is It Anyway? A Manual for Decolonization provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation. This audio version features renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. The late Arthur Manuel’s writings are read by his grandson, Mahekan Anderson.
OCLC: 1122613551
Keywords: 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Decolonization is not a Metaphor - Tuck, Eve; K. Wayne Yang (Journal Publishing Services, 2012)
Our goal in this article is to remind readers what is unsettling about decolonization. Decolonization brings about the repatriation of Indigenous land and life; it is not a metaphor for other things we want to do to improve our societies and schools. The easy adoption of decolonizing discourse by educational advocacy and scholarship, evidenced by the increasing number of calls to “decolonize our schools,” or use “decolonizing methods,” or, “decolonize student thinking”, turns decolonization into a metaphor. As important as their goals may be, social justice, critical methodologies, or approaches that decenter settler perspectives have objectives that may be incommensurable with decolonization. Because settler colonialism is built upon an entangled triad structure of settler-native-slave, the decolonial desires of white, non-white, immigrant, postcolonial, and oppressed people, can similarly be entangled in resettlement, reoccupation, and reinhabitation that actually further settler colonialism. The metaphorization of decolonization makes possible a set of evasions, or “settler moves to innocence”, that problematically attempt to reconcile settler guilt and complicity, and rescue settler futurity. In this article, we analyze multiple settler moves towards innocence in order to forward “an ethic of incommensurability” that recognizes what is distinct and what is sovereign for project(s) of decolonization in relation to human and civil rights based social justice projects. We also point to unsettling themes within transnational/Third World decolonizations, abolition, and critical space-place pedagogies, which challenge the coalescence of social justice endeavors, making room for more meaningful potential alliances
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Indigenous Methodologies: Characteristics, Conversations, and Contexts - Kovach, Margaret (University of Toronto Press, 2009)
"An innovative and important contribution to Indigenous research approaches, this revised second edition provides a framework for conducting Indigenous methodologies, serving as an entry point to learn more broadly about Indigenous research."–
OCLC: 1223012487
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé